Glass fracture by focusing of laser-generated nanosecond surface acoustic waves. (1st January 2019) - Veysset, David; Kooi, Steven E.; Haferssas, Ryadh; Hassani-Gangaraj, Mostafa; Islam, Mohammad; Maznev, A.A.; Chernukha, Yevheniia; Zhao, Xiaoguang; Nakagawa, Keiichi; Martynowych, Dmitro; Zhang, Xin; Lomonosov, Alexey M.; et al.
Abstract: Dynamic fracture of borosilicate glass through focusing of high-amplitude nanosecond surface acoustic waves (SAWs) at the micron scale is investigated in an all-optical experiment. SAWs are generated by a picosecond laser excitation pulse focused into a ring-shaped spot on the sample surface. Interferometric images capture the SAW as it converges towards the center, focuses, and subsequently diverges. Above a laser energy threshold, damage at the acoustic focal point is observed. Numerical calculations help us determine the time evolution of the stress distribution. We find that the glass withstands a local tensile stress of at least 6 GPa without fracture. Graphical abstract: Unlabelled Image